Hazardous waste management at University of Limpopo (Turfloop Campus) : Is it managed according to legal standards? - Mbeki, Unathi Namhla (University of Limpopo (Turfloop Campus), 2009)
In this study hazardous waste is defined as well as its classes.The current status of hazardous waste management, available legislation,enforcement and minimum requirements are discussed.Hazardous waste chemicals produced at University of Limpopo (Turfloop Campus),their amounts and their management were determined.They are compared to minimum requirements from Department of Water Affairs and Forestry.Other Universities hazardous waste management programmes were looked at.
Thesis (M.Phil. (Environmental Law and Management)) --University of Limpopo, 2009
Keywords: Waste management; Harzadous wastes law; Hazardous wastes -- Management; Hazardous wastes -- Law and legislation -- South Africa